Experimental tests on strengthening strategies for masonry infill walls: a literature review - Furtado, André (2020)
The masonry infill walls’ seismic behaviour is being characterized by extensive damages and out-of-plane (OOP) collapses due to combined in-plane and OOP loading demands. Several efforts are being made to develop efficient strengthening strategies to reduce their seismic vulnerability and in particular to prevent the panels’ collapse. The present manuscript aims presenting retrofit and strengthening strategies to improve the infill masonry walls seismic performance, with particular attention to the prevention of the OOP collapse. Retrofit and improvement of infill walls seismic behaviour is a complex subject, since it cannot be disconnected from their effect on the overall building response. It is paramount to assume that the strengthening should be effective under seismic actions in the plane of the infill wall and under transverse loadings. A systematic review was carry out focusing the major findings and observations made by each author are presented. For each technique, a summary table is provided containing the details regarding the strengthening strategy adopted, major results and observations.